We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
90
3
avatar

If \(f(x)=\dfrac{a}{x+2}\) , solve for the value of \(a\) so that \(f(0)=f^{-1}(3a).\)

 Feb 17, 2019
edited by Guest  Feb 17, 2019
edited by Guest  Feb 17, 2019
edited by Guest  Feb 17, 2019
 #1
avatar
0

please help anyone???

 Feb 17, 2019
 #2
avatar+311 
+2

Hey there guest.

f(0)=a/2

note that f^-1 is the recipricol of f

knowing that, f(3a)=a/3a+2. f^-1(3a)= 3a+2/a

 

f(0)=f^-1, so a/2=3a+2/a. Cross multiplying gives a^2=6a+4

a^2-6a-4=0

 

Completing the square time:

a^2-6a+9=13

(a-3)^2=13

a-3=+/-sqrt13

a=+/-sqrt3 + 3

Hope this helps

 Feb 17, 2019
 #3
avatar+27775 
+1

f-1 means inverse rather than reciprocal, so if f(x) = a/(x+2) then f-1(x) = a/x - 2

 

f(0) = a/2

f-1(3a) = 1/3 - 2 = -5/3

 

So a/2 = -5/3 or a = -10/3

 Feb 17, 2019

23 Online Users

avatar
avatar
avatar